As if History teaching were also history: considerations in light of the tools we use to understand the past: (Tempo e Argumento, 2021)
This paper attempts to analyze a particular corpus of texts related to the didac-tics/teaching of history from perspectives seldom explored in this field, such as concep-tual history, intellectual history and other contributions from philosophy of history. This will be developed in three parts. The first will deal with the diversity of content attribut-ed to expressions such as history teaching or history didactics, which focus both on con-ceptualizations and suggestions regarding what history to teach, how to teach it, how history is learned, why and what for teach it, in a setting where the relationships between the teaching of history and historiography or philosophy of history are approached dif-ferently. The second will focus on the usually implied means in which what constitutes the object of the writings related to the teaching of history is seized, with particular em-phasis on the forms in which the texts conceive causality or interdependence relation-ships between history curricula, textbooks, teachers’ teaching and student’s learning of history. Drawing closure to the cycle of this reflection the third part will be devoted to brief analysis on some texts referring the goals of teaching history.Keywords: history teaching; history didactics; history teaching-learning.